Characterization of the intramolecular G‐quadruplex promoting activity of Est1. Issue 6 (30th January 2013) - Li, Qian-Jin; Tong, Xia-Jing; Duan, Yi-Min; Zhou, Jin-Qiu
Abstract : In the budding yeast Saccharomyces cerevisiae, telomeric DNA includes TG1–3 /C1–3 A double‐stranded DNA and a protruding G‐rich overhang. Our previous studies revealed that the telomerase regulatory subunit Est1 promotes telomeric single‐stranded DNA to form intermolecular G‐quadruplex in vitro, and this activity is required for telomere replication and protection in vivo. In this study, we further characterized the G‐quadruplex promoting activity of Est1. Here we report that Est1 is able to promote the single‐stranded oligonucleotide of (TGTGTGGG)4, which mimics the natural telomeric DNA, to form intramolecular G‐quadruplex. Therefore, it remains possible that the intramolecular G‐quadruplex promoting activity of Est1 is biologically relevant in telomere replication in vivo. Abstract : ► Est1 promotes ssDNA containing four GGG‐tracts to form intramolecular G‐quadruplex in vitro. ► Mutation at the EF‐hand motif of Est1 leads to reduced G‐quadruplex promoting activity. ► ssDNA concentration affects Est1's inter‐ and intramolecular G‐quadruplex promoting activity. ► Est1 cannot promote ssDNA lacking four GGG‐tracts to form the intramolecular G‐quadruplex.